Identification and Molecular Characterization of B-Tubulin Gene from Dermatophyte Pathogen Microsporum Canis - Uthman, Aumaid U. (Sulaimani Journal for Pure and Applied Sciences, 2007)
Microsporum canis is the most common pathogen causing dermatophytosis in dogs and cats, which can transmit the pathogen to humans. The disease is increasing in many European countries. Studies regarding the structure, expression, and organization of M. canis genes have been relatively limited because of it's non-aggressive and non-life threatening nature. Microtubules are essential cytoskeleton polymers in all eukaryotes. They are made of α and β-tubulin heterodimers. In this study the DNA and the structural organization of β-tubulin gene of M. canis is described. The DNA of 2487 bp has been identified and sequenced. The ORF of 1341 bp encoding a protein of 447 amino acids with a molecular weight of 49.8 kD is interrupted by eight introns (56-187bp). The gene is highly homologous to β-tubuli of Trichophyton rubrum (%98) and A spergillus parasticus (%91). This data may form one of the bases for the development of molecular investigation of dermatophyte fungi M. canis.
Keywords: Microsporum canis; Dermatophytes; βtubulin; gene expression